Hubungan Tingkat Aktivitas Fisik dengan Angka Kejadian Overweight pada Anak Usia 7-8 Tahun di MI Al-Jihad Palangka Raya - Aziz Wicaksono; Vina Agustina; Prinawati Prinawati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Introduction: According to the World Health Organization (WHO), overweight affects nearly one in three school children aged 6-9 years. Overweight marks the crucial upper limit of obesity. One of the causes of overweight is physical activity. A decrease in children's physical activity level may lead to an increase in the incidence of overweight. Based on the results of a preliminary survey at MI Al-Jihad Palangka Raya. 7 out of 8 students were found to be overweight with a low level of physical activity, this shows the high influence of physical activity on the incidence of overweight which is quite clear. The purpose of this study was to determine and analyze the relationship between physical activity level and the incidence of overweight in children aged 7-8 years at MI Al-Jihad Palangka Raya. Methods: Non-experimental quantitative research using a correlational design with a cross sectional approach. The sample was 47 children using random sampling method. The measuring instruments used were questionnaires for physical activity level and nutritional status (BMI) from anthopometric examination using microtoa and scales for the incidence of overweight. In bivariate analysis, the statistical analysis test used was spearman rank. Results: The findings of the study were that the most respondents with mild physical activity levels (61.7%) and normal nutritional status (76.6%). The results of the spearman rank test obtained a significance value of p-value of 0.000 and smaller than the significance level of 0.05 and a correlation value of 0.895 close to 1. Discussion: The significance value of p-value <0.05 indicates that H0 is rejected H1 is accepted, which indicates that the variable level of physical activity has a significant correlation with the incidence of overweight in children aged 7-8 years at MI Al-Jihad Palangka Raya. The correlation value is close to 1, indicating that the relationship between the two variables is very strong.